Cloning and molecular characterization of the ORF5 gene from a PRRSV-SN strain from Southwest China. (November 2017) - Chen, Xi-Wen; Li, Lian; Yin, Miao; Wang, Qian; Luo, Wen-Tao; Ma, Ying; Pu, Zhong-Hui; Zhou, Jie-Long
Abstract: To monitor the genetic variation of PRRSV, the ORF5 gene of the PRRSV-SN strain found in Suining City, Sichuan Province, was cloned and sequenced. The results showed that the PRRSV-SN strain was a highly pathogenic PRRSV (HP-PRRSV) variant strain with the North American (NA) genotype. Homology analysis showed that the ORF5 gene of the PRRSV-SN isolate shared 89.4% (86.5%) nucleotide (amino acid) sequence similarity with the North American strain VR-2332, 98.8% (96%) similarity with JXA1, and 63.8% (57.7%) similarity with the European type representative strain Lelystad virus. Phylogenetic analysis showed that PRRSV-SN belongs to the NA genotype and has the same subtype as other highly pathogenic PRRSV strains. Amino acid sequence analysis showed that compared with the VR2332 strain, PRRSV-SN has different degrees of variation in the signal peptide, transmembrane region (TM), primary neutralizing epitope (PNE), non-neutral epitopes and N-glycosylation sites. Antigenicity analysis showed that the PRRSV-SN ORF5 gene products and JXA1 have similar antigenic characteristics, and the antigenic epitopes are mainly located in aa30-39, aa50-60, aa128-141, aa146-155 and aa161-183 regions. In contrast, the antigenic characteristics of PRRSV-SN are quite different from those of the VR2332 strain. The main differences were that the PRRSV-SN strain was significantly narrower than the VR2332 strain in the aa30-39 and the aa50-60 regions but was significantly wider in the aa136-141 region. The results of this study showed that the epidemic strains that cause PRRSV outbreaks in the farm are still mainly JXA1 variants, but due to the more frequent use of live vaccine immunizations, the genes of the PRRSV epidemic strain still show constant variation. Vaccination with live PRRSV should be reduced, and surveillance of PRRSV strains should be enhanced. Highlights: We cloned and analyzed the PRRSV-SN strain ORF5 complete gene sequence obtained from PRRSV disease outbreaks in China. We analyzed the molecular characterization and genetic evolution of ORF5 gene of PRRSV-SN strain. We found that the PRRSV-SN strain was closely related to the JXA1 strain, but had undergone considerable variation.